Towards the development of a curriculum to train behavior analysts to provide services via telehealth. Issue 2 (31st January 2022) - Neely, Leslie; Tsami, Loukia; Graber, Jessica; Lerman, Dorothea C.
Abstract : The COVID‐19 pandemic has led to a dramatic increase in behavior analysts' use of telehealth services. Nonetheless, no research has evaluated the skills or training needed for therapists to provide these services effectively. The purpose of this study was to develop and evaluate a curriculum for providing high‐quality, parent‐training telehealth services. Four in‐service Board Certified Behavior Analysts® (BCBAs®) who received brief behavioral skills training on this curriculum reached 100% fidelity within four sessions. The skills generalized to a novel family and maintained nearly 1 year after the training. All participants rated the training as highly acceptable and effective. The independent ratings of 4 in‐service BCBAs, blinded to the study conditions, also supported the social validity of the outcomes. This curriculum may be considered an initial step towards development of competency for interventionists providing ABA services via telehealth. Further research is warranted as demand for telehealth services continues to grow.